2022
DOI: 10.1021/acs.inorgchem.2c00419
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Aromatic Hydroxylation Catalyzed by the Iron-Dependent Hydroxylase PqqB Involved in the Biosynthesis of Redox Cofactor Pyrroloquinoline Quinone

Abstract: PqqB from Methylobacterium extorquens is a unique nonheme iron-dependent hydroxylase involved in the biosynthesis of redox cofactor pyrroloquinoline quinone (PQQ). A series of recent experiments have demonstrated that PqqB catalyzes the stepwise insertions of two oxygen atoms into the tyrosine ring of the diamino acid substrate, generating the quinone moiety of PQQ; however, the reaction details have not been elucidated yet. In this paper, on the basis of the crystal structures, the enzyme− substrate complex m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Moreover, experimental studies on the analogous nonheme iron dioxygenases taurine/α-ketoglutarate dioxygenase (TauD) and prolyl-4-hydroxylase (P4H) also characterized their iron(IV)-oxo species as high-spin. , This implies that these nonheme iron and α-ketoglutarate-bound enzymes all form a similar active species with analogous ligand coordination and environment. Computational studies on enzymatic nonheme iron(IV)-oxo structures supported these assignments and reported high-spin ground states in all cases. As the septet spin state is significantly higher in energy than the quintet spin state, it was not considered further in this work.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, experimental studies on the analogous nonheme iron dioxygenases taurine/α-ketoglutarate dioxygenase (TauD) and prolyl-4-hydroxylase (P4H) also characterized their iron(IV)-oxo species as high-spin. , This implies that these nonheme iron and α-ketoglutarate-bound enzymes all form a similar active species with analogous ligand coordination and environment. Computational studies on enzymatic nonheme iron(IV)-oxo structures supported these assignments and reported high-spin ground states in all cases. As the septet spin state is significantly higher in energy than the quintet spin state, it was not considered further in this work.…”
Section: Resultssupporting
confidence: 89%
“…60 The wider field of iron-containing enzymes also continues to be a fruitful target for QM/MM studies. [61][62][63][64][65][66][67][68][69][70][71][72][73] In recent work Tian et al have studied the unique non-haem iron enzyme ergothioneine synthase, using QM/MM to identify oxygen binding modes, determine the preferred spin state for reactivity, and clarify the sequence of sulfoxidation and C-S bond formation in its catalytic cycle. 74 The 2-oxoglutarate (2OG) dependent non-haem iron oxygenases catalyse a wide variety of oxidative processes and have been the target of multiple recent studies.…”
Section: Qm/mm Simulations Of Biomoleculesmentioning
confidence: 99%